12 mJ pulse energy 8-channel divided-pulse ultrafast fiber-laser system - Mueller, Michael; Kienel, Marco; Klenke, Arno; Gottschall, Thomas; Shestaev, Evgeny; Ploetner, Marco; Limpert, Jens; Tuennermann, Andreas (Proceedings of SPIE - The International Society for Optical Engineering, 2017)
State-of-the-art ultrafast fiber lasers currently are limited in peak power by excessive nonlinearity and in average power by modal instabilities. Coherent beam combination in space and time is a successful strategy to continue power scaling by circumventing these limitations. Following this approach, we demonstrate an ultrafast fiber-laser system featuring spatial beam combination of 8 amplifier channels and temporal combination of a burst comprising 4 pulses. Active phase stabilization of this 10-armed interferometer is achieved using LOCSET and Hänsch-Couillaud techniques. The system delivers 1 kW average power at 1 mJ pulse energy, being limited by pump power, and delivers 12 mJ pulse energy at 700 W average power, being limited by optically induced damage. The system efficiency is 91% and 78%, respectively, which is due to inequalities of nonlinearity between the amplifier channels and to inequality of power and nonlinearity between the pulses within the burst. In all cases, the pulse duration is ∼260 fs and the M2-value is better than 1.2. Further power scaling is possible using more amplifier channels and longer pulse bursts.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Chirped-pulse amplification; Coherent beam combining; Divided-pulse amplification; Hänsch-Couillaud; LOCSET; Ytterbium fiber laser